Regional postdeforestation weathering feedback drove diachronous C–S cycle perturbations during the end-Permian crisis - Jianbo Chen; Binjian Lu; Longye Du; Mang Lin; Shu-zhong Shen; Isabel P. Montañez; Zhuo Feng (Proceedings of the National Academy of Sciences, 2025)
The Permian–Triassic (P-Tr) transition (~252 Ma) witnessed Earth’s most severe biocrisis, which has long been linked to Siberian Traps volcanism and associated environmental upheaval. Major perturbation of the global carbon (C) and sulfur (S) cycles is mainly inferred from marine δ 13 C and δ 34 S records, whereas few existing terrestrial records link δ 34 S fluctuations to widespread dispersal and fallout of volcanogenic sulfate aerosols. Mounting evidence, however, reveals that the collapse of P-Tr terrestrial ecosystems was diachronous, questioning a hypothesized globally synchronous common forcing. Here, we present records of pyritic multiple-S isotopes (δ 34 S py and Δ 33 S) and bulk organic δ 13 C for a paleotropical peatland drill core (HK-1) from Southwest China. The δ 34 S py variations define three distinct phases with a notable decline in δ 34 S py across the P-Tr transition, suggesting substantially elevated terrestrial sulfate influx coincident with major carbon cycle perturbation. Notably, overall small positive Δ 33 S values (+0.01 to +0.12‰) rule out a dominant role for stratospheric sulfates. Collectively, the observed changes in δ 13 C org , δ 34 S py , and Δ 33 S support catastrophic collapse of the Cathaysian Flora leading to intensified weathering and sulfate release. This inferred event, slightly after the P-Tr marine extinction, postdates by several 100-ky terrestrial floral collapse and perturbation of the C–S cycles documented in the high-latitude Sydney Basin. Cross-latitudinal diachroneity of terrestrial ecosystem collapse and consequent C–S perturbation challenges the hypothesis of a single, global volcanic driver. Rather, regional deforestation and its cascading effects overprinted on the global perturbations of biogeochemical cycles emerge here as critical factors shaping Earth’s largest recorded crisis.